Polyacrylonitrile/lignin sulfonate blend fiber for low-cost carbon fiber. Issue 53 (11th June 2015) - Dong, Xiaozhong; Lu, Chunxiang; Zhou, Pucha; Zhang, Shouchun; Wang, Liyong; Li, Denghua
<x xml:space="preserve">Abstract</x> Polyacrylonitrile/lignin sulfonate blend fiber spun via wet spinning process could be stabilized rapidly, and thus suitable to produce a low-cost carbon fiber.